ENT 530 Social Media Portfolio: Karl's Caramel Popcorn By Aiyu / Nor'ai Mohammad - Mohammad, Nor'ai (2021)
#satufamilysatukiloKARLCARAMELPOPCORN is a trademark for Karl’s Caramel Popcorn By AiYu. Our business started on April twelve in 2021. My business objective is to offer popcorn served in a caramel flavor at an affordable price and a luxurious caramel. This homemade caramel popcorn will definitely captivate the heart of our customers consisting of teenagers, adults and children. This group became our target because they are definitely people who love sweetness. Our regular customer keeps on repeating their order as each of our caramel popcorn will be popped in every bite and taste its caramel. This indirectly will make our customer never disappoint with the taste and differ with other competitors. Our marketing strategy is primarily to provide products that will satisfy our customers and feel worth it with their money spend. Since our opening, we have managed to sell nearly 70 packs of caramel popcorn. This shows that Karl’s Caramel Popcorn is a marketable product and able to maintain its growth to compete with other competitors. In order to expand our marketing strategy, we see social media as a great platform to market our caramel popcorn. Therefore, we have developed a Facebook page namely “Karl’s Caramel Popcorn By AiYu”. Through this social media platform, we are confident that we will attracts more customers to know our product existence. In addition, to complete the objective, we have post teasers, soft sell and hard sell. Teaser for people get excited and curious to know what we will promote. Soft sell for people to be more interested to our product by knowing some story, facts, history and others. Next is hard sell, from this people will get information about our products details. We believe that by developing social media and making posts such as teasers, soft sells, and hard sells will be able to achieve our objectives. We will provide our information in detail to ensure that our customer will not be left behind with our products namely prices, calls to action, and other services of what we provide. Nowadays, people prefer something that is easy to serve or ready to eat and will make their life easier and more enjoyable. Therefore, we have completed our objectives.